6 - L’Islam et la femme dans l’espace public au Niger: https://doi.org/10.4314/ad.v34i3-4.63531 - Alio, Mahaman (Africa Development, 2009)
The aim of this paper is to show how women in Niger have negotiated their citizenship in a country the population of which is 99 per cent Muslim. Right from independence, one could see the balancing game which former president Diori Hamani played to maintain the secularity of the state and the citizens’ rights. In 1975, taking advantage of the International Woman Year, women came into the public sphere, and have since then continued to demand their rights.The democratization of the Niger society, stemming from the 1991 National Conference, has brought in the public sphere Muslim and Christian associations with their own demands. What distinguished these movements from what the Niger State was used to was that they brought new issues in the public sphere, especially religious ones. The intellectual elite also played their enlightening role in this debate. All these different citizenship movements led to the consideration of women and their political choices despite religious interferences.